Cognitive Biases and Investment Decision Making: With Reference to Butwal Sub-metropolitan City (The Lumbini Journal of Business and Economics, 2025)
Purpose: This study explores how different types of cognitive biases influence investors’ decisions making in Butwal City.Methods: The study used a causal-comparative research design to examine the relationship between dependent and independent variables. Data were collected from 384 respondents using structured with a detailed seven point Likert scale and a non-probability sampling method. Quantitative analysis included both descriptive and inferential statistics including mean, standard deviation, correlation, Independent sample t test, Annova and regression analysis using the PLS-SEM method.Results: The results shows that loss-aversion bias and herding bias play a major role in investment decisions It also showed that gender influences the link between cognitive bias and investment choices. However, overconfidence and representative bias were not found to have a significant impact on investment decisions making. Conclusion: Investors should acknowledge how loss aversion and herding bias influence their ability to make effective investment decision making.